(untitled) (Journal of Management and Business Education, 2019)
This letter introduces the issue 2 (2019) of the Journal of Management and Business Education. The issue consists of five works related to: the evaluation of teamwork; the use of the press for active learning; the skills necessary to face teaching in the next decade; entrepreneurial education in the university; and inspiring education. In addition, the collaboration is appreciated to all those who have made possible the publication of this number.